The Effect of Planting Systems and Planting Methods on the Growth and Yield of Inpago Unsoed Protani Rice Variety - Indrianingsih, Citra; Barokah, Umi (Badan Penerbitan Fakultas Pertanian (BPFP), Fakultas Pertanian, Universitas Bengkkulu, 2024)
For the Indonesian people, rice is indispensable as it provides essential energy and carbohydrates. One critical factor influencing rice production is the planting system and planting methods. The research aimed to determine the effect of different planting systems on the growth and yield of the Inpago Unsoed Protani rice variety (Oryza sativa L.). Conducted in Gintungan Village, Gebang District, Purworejo Regency, from June 2023 to October 2023, the study utilized a Split Plot Design with 3 replications. The main plot was planting method consisting of Tile planting system (25 cm x 25 cm), Jajar Legowo planting system 2:1 (20 cm x 10 cm x 40 cm), and Jajar Legowo planting system 2:1 (25 cm x 12.5 cm x 50 cm). The subplot was the number of seedlings เว็บสล็อต | R4shub per hole, including 1, 2, and 3 seedlings per planting hole. Observations focused on plant height, number of productive tillers, number of panicles, number of filled grains, amount of empty grain, number of filled grains per panicle, weight of 1000 grains, and yield. The results showed no interaction effect between the planting system and the number of seedlings on the growth and yield of the Inpago Unsoed Protani rice variety. However, the Jajar Legowo planting systems outperformed the tile planting systems, demonstrating superior results. Specifically, employing a single seedling per hole proved to be the optimal planting method for enhancing the growth and yield of the Unsoed Protani rice variety. Keywords: planting method, rice, plant system